2003
DOI: 10.1037/0022-006x.71.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Individuation, peers, and adolescent alcohol use: A latent growth analysis.

Abstract: The study used latent growth modeling to investigate longitudinal relationships between individuation, peer alcohol use, and adolescent alcohol use among African American, Mexican American, and non-Hispanic White adolescents (N = 6,048) from 7th, 8th, and 9th grades over a 3-year period. Initial levels of peer alcohol use were significantly related to changes in adolescents' alcohol use, whereas initial adolescent alcohol use also significantly related to changes in peers' alcohol use, suggesting a bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 68 publications
6
46
0
2
Order By: Relevance
“…However, this internalized peer pressure was found to be less of a risk factor than the external peer pressure of actually being urged or pressured by peers to act in a certain way, such as engaging in substance use (Santor et al 2000). While children's perspectives on substance use may be initially set by the family, they are reinforced through the peer group, with whom most drinking, and nearly all illicit substance abuse occurs (Bray et al 2003). Peer influence is one of the most prominent factors associated with adolescent smoking and drinking (Simons-Morton et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…However, this internalized peer pressure was found to be less of a risk factor than the external peer pressure of actually being urged or pressured by peers to act in a certain way, such as engaging in substance use (Santor et al 2000). While children's perspectives on substance use may be initially set by the family, they are reinforced through the peer group, with whom most drinking, and nearly all illicit substance abuse occurs (Bray et al 2003). Peer influence is one of the most prominent factors associated with adolescent smoking and drinking (Simons-Morton et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Recent work has begun to assess younger teens, however, most studies are cross-sectional (e.g., [8,18]), or longitudinally focus on only one substance, such as cigarettes [19] or alcohol [20]. A recent cross-sectional examination of both peer and parent influences on seventh graders' use of cigarettes, alcohol, and marijuana and their sexual behavior found that perception of peer use was related to increased tobacco and alcohol use [8].…”
mentioning
confidence: 99%
“…We also expected that although current use would contribute to future use, perception of peer use would still be significantly positively related to use. As young adolescent substance involvement has been found to differ by gender [22,25], ethnicity [20], and age [25], we included these as covariates.…”
mentioning
confidence: 99%
“…Jugendliche, die besonders empfänglich für den Einfluss ihrer engen Freunde sind, scheinen besonders gefährdet, wenn diese sie in Richtung Drogen und Alkohol drängen (Allen et al 2006), und das gilt wie beim aggressiven Verhalten insbesondere dann, wenn der Druck von Jugendlichen mit hohen Status in der PeerGruppe ausgeübt wird (Allen et al 2012). Es gibt auch Belege dafür, dass sich die Trinkgewohnheiten von Jugendlichen und der Alkoholkonsum ihrer Freunde im Verlauf der Zeit wechselseitig zu beeinflussen scheinen, sodass das Trinken unter Freunden oft eskaliert (Bray et al 2003;Popp et al 2008;Poulin et al 2011).…”
Section: Alkohol Und Drogenmissbrauchunclassified